The moral status of civil disobedience - Brownlee, K (2007)
﻿ This dissertation examines the moral character of civil disobedience. The discussion begins with a conceptual analysis of civil disobedience which eschews standard definitions in favour of a paradigm case approach, highlighting a parallel between the communicative aspects of civil disobedience and the communicative aspects of lawful punishment by the state. Foundations for a moral evaluation of civil disobedience are then laid down through, first, an examination of the nature of wrongdoing and justification, and second, a critique of contemporary defences of political obligation. The absence of political obligation, it is argued, does not immediately justify civil disobedience even in reprehensible regimes because, in all contexts, adherence to the law and disobedience of the law must be judged on the basis of their character and consequences. Various considerations relevant to the justifiability of civil disobedience are then examined before the discussion turns to the three principal claims defended in this thesis. The first is that people have a moral right to engage in civil disobedience irrespective of both the political regime and the merits of their cause. The second is that the reasons for which people engage in civil disobedience may be understood in terms of a pursuit of ideals. When motivated by a deep commitment to the genuine ideals of their society, disobedients may be said to demonstrate responsible citizenship. The third claim is that the law should treat disobedients differently from other offenders. When civil disobedience is morally justified, and sometimes when it is not, the law has reason to be lenient to its practitioners. In defending these claims, this discussion critiques not only the 'classical' narrow conception of civil disobedience as a public, non-violent, conscientious breach of law for which disobedients are willing to be punished, but also broader conceptions of civil disobedience which take a modest view of its justifiability and accord it limited status as a moral right.